(untitled) (Revista Brasileira Multidisciplinar, 2025)
In Brazil, e-SUS APS represents the main computerization strategy for Primary Care, committed to qualifying health information and care management. The objective of this study was to understand the operationalization of e-SUS regarding registration, monitoring and evaluation from the perspective of multidisciplinary teams in the city of Recife – PE. This is an exploratory study, with a qualitative approach, carried out with eight professionals from multidisciplinary teams from Health District I, Recife – PE. Data were collected through interviews with a semi-structured script and analyzed according to Content Analysis. The results indicate that computerization in PHC is still compromised by the lack of equipment and structure, coupled with poor compatibility with the dynamics of eMulti. Despite this, e-SUS is considered a promising resource for PHC care.